A study on the relationship between total quality management (TQM) practices and employee innovation / Suraya Ismail - Ismail, Suraya (2016)
The purpose of this study is to investigate the relationships between six factors of TQM practices and the employee's innovation. The six factors of TQM practices are leadership, strategic planning, customer focus, information & analysis, people management and process management. Method used for this study is correlational research in order to examine the relationship between variables. Simple random sampling has been applied as a sampling technique that used in this study with 56 respondents as the sample size which from all department at Universiti Tenaga Nasional (UNITEN) Kampus Sultan Haji Ahmad Shah (KSHAS). The finding result shows all the factors of TQM practices have significant relationship towards employee's innovation. People management is most influence employee innovation because it has the less mean and closest to become the high influencing variable.